Comparison of Bacteriological Profiles from wound Swab Isolates among Hospital Acquired Infection and Community Acquired Infection in a Tertiary Care Hospital, Bangladesh - Jahan, Tarana; Yusuf, Md Abdullah; Shahid, Sazzad Bin; Sultana, Sharmeen; Mollika, Ferdows Ara; Rahman, Md Mostaqimur (Bangladesh Journal of Medical Microbiology, 2023)
Background: Wound infection is one of the health problems that are caused and aggravated by the invasion of pathogenic organisms. Objective: The objective of the study was to compare the bacteriological profiles including antimicrobial sensitivity patterns from wound swab isolates among hospital-acquired infection and community-acquired infection so that recommendations can be made for preventing resistance and empirical antibiotic treatment. Methodology: This retrospective study was conducted in the Department of Microbiology at Monno Medical College, Manikganj, Bangladesh during the period from June 2020 to July 2021 for a duration of one year. The patients attending the outpatient department were represented as community-acquired infection and patients admitted at least 48 hours were represented as hospital-acquired infection. All the samples were inoculated on blood agar and Mac Conkey agar media for 24 to 48 hours at 35 to 37°C. Organisms were identified by standard microbiological procedures. An antimicrobial susceptibility test was done for all isolated bacteria by the disc diffusion method. Results: A total number of 170 patients were recruited among them hospital-acquired infection was predominant at 96(56%) patients and community-acquired infection was at 87(49%) patients. About 126 (74.1%) yielded growth of different bacteria and culture-positive cases were found in 78 (61.9%) in the HAI group. The predominant isolate is Staphylococcus aureus majority were found in the HAI than CAI which was 36(57.1%) and 27(42.9%) respectively. Followed of Escherichia coli majority were found in the HAI than CAI which was 17(68.0%) and 8(32.0%) respectively. Streptococcus pyogenes were found 11(61.1%) of the HAI, Pseudomonas species majority were found in the HAI than CAI which was 10(62.5%) and 6(37.5%) respectively and Klebsiella species were found in the HAI 4 (100.0%). Staphylococcus aureus was found highly sensitive to sulphamethoxazole (100%), imipenem (79.4%), and gentamicin(76.2%). Escherichia coli was found highly sensitive to sulphamethoxazole (100%), ceftazidime (100%), and gentamicin (100%). Conclusion: Staphylococcus aureus was the most frequently isolated pathogen from wound swab among both HAI & CAI. Antibiotic sensitivity patterns of various isolates will guide for appropriate selection of antibiotics to reduce the spread of resistant bacteria against wound infection. Bangladesh Journal of Medical Microbiology, July 2022;16(2):53-59